2004
DOI: 10.1002/mame.200400127
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Particle Matrix Adhesion on the Mechanical Properties of Silica Filled Cyanate Ester Composites

Abstract: Summary: The effect of silica and its surface treatment on the mechanical properties of composites was studied as part of the evaluation of cyanate ester matrices as potential electronic encapsulants. Three filler surface treatments were used, as a qualitative interfacial adhesion scale, in an attempt to gauge the magnitude of interfacial adhesion between untreated filler and the cyanate ester matrix. There was strong interfacial adhesion between matrix and untreated filler. The level of silica content most af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…The addition of fumed silica without significant chemical bonding to the matrix at the loading levels (up to about 5% by weight) used in this study would not be expected to alter the stiffness characteristics of the networks by much. However, the use of this particle type could have a positive influence on fracture toughness, 28 although in this case also the loading levels are lower than those typically employed when Figure 11. T G before and after exposure to 85°C water for 96 h as determined by dynamic TMA for silanol (a), octyl (b), and 3-amino (c) surface types.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 96%
“…The addition of fumed silica without significant chemical bonding to the matrix at the loading levels (up to about 5% by weight) used in this study would not be expected to alter the stiffness characteristics of the networks by much. However, the use of this particle type could have a positive influence on fracture toughness, 28 although in this case also the loading levels are lower than those typically employed when Figure 11. T G before and after exposure to 85°C water for 96 h as determined by dynamic TMA for silanol (a), octyl (b), and 3-amino (c) surface types.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 96%
“…Uniform distribution of the binary phases in 30 wt% PES sample may be hindered due to the high viscosity of the melt . To overcome this problem, various research groups previ-ously used solution casting techniques as an approach to achieve an equilibrium microstructure in blends, even at high PES concentrations [12,17].…”
Section: Results and Discussion 31 Morphology Of Becy/pes Blendsmentioning
confidence: 99%
“…While the current efforts to develop new thermoset resins with advanced thermal and mechanical properties were based on new synthesis routes [9,10], blending of polymers offers a simple and easy alternative over complex synthesis techniques. Multiphase polymer blends prepared to create or improve desired functional properties in thermoset polymers are considered potential alternatives in the literature [11][12][13][14]. In the present work, poly(ether sulfone) (PES) was used as a high temperature resistant thermoplastic toughening agent for BECy.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, functionalizing agents used to treat silica particles were found to slightly enhance properties compared to non-functionalized particles [65].…”
Section: Property Enhancement Via Nanofillersmentioning
confidence: 99%